Multifunctional, Sustainable, and Biological Non-Ureolytic Self-Healing Systems for Cement-Based Materials. (June 2022) - Fahimizadeh, Mohammad; Pasbakhsh, Pooria; Mae, Lee Sui; Tan, Joash Ban Lee; Raman, R.K. Singh
Highlights: Non-ureolytic concrete self-healing is a path to sustainable construction. Waste materials can be used in the self-healing systems and as cement replacement. Non-ureolytic systems can improve the durability and the service life of structures. Genetic modification strategies can expand the self-healing potential of the bacteria. Non-ureolytic systems can be engineered for different environments and conditions. Abstract: Microbially induced calcium carbonate (CaCO3 ) precipitation (MICP) has been investigated as a sustainable alternative to conventional concrete remediation methods for improving the mechanical properties and durability of concrete structures. To date, urea-dependent MICP is the most widely employed MICP pathway in biological self-healing concrete research as its use has resulted in efficient CaCO3 precipitation rates. NH3 is a byproduct of ureolysis, and can be hazardous to cementitious structures and the health of various species. Accordingly, non-ureolytic bacterial concrete self-healing systems have been developed as eco-friendly alternatives to urea-dependent self-healing systems. Non-ureolytic pathways can improve the physical properties of concrete samples and incorporate the use of waste materials; they have the potential to be cost-effective and sustainable. Moreover, they can be applied in terrestrial and marine environments. To date, research on non-ureolytic concrete self-healing systems has been scarce compared to that on ureolytic systems. This article discusses the advances and challenges in non-ureolytic bacterial concrete self-healing studies and highlights the directions for future research.